Invasive alien species in the Campos Sulinos: Current status and future trends - Guido, Anaclara (2023)
The dramatic loss of natural grasslands in the Campos Sulinos , and the threats to the remaining areas due to biological invasions, makes it essential to compile information on which are the most frequent invasive alien species (IAS) and their distribution throughout the region. In this chapter, we provide an overview of the main aspects of biological invasions in the Campos Sulinos region. We begin with a brief introduction, setting the scene and providing the required context and main concepts. Based on data from national and international databases of IAS occurring in Brazil, we present a general distribution pattern of the level of invasion in the Campos Sulinos , indicating the most invaded areas and the most frequent IAS. We present examples of their introduction pathways, highlighting some human uses, the key factors involved in the process, the wide range of impacts, and discuss some of the challenging management actions. The chapter ends with a brief reflection about the future of the invasions in Campos Sulinos according to global change scenarios, and some recommendations to move forward in IAS management.